AN OVERVIEW OF THESIS STUDIES IN ACCOUNTING ETHICS - Gül, Meltem (PressAcademia, 2024)
Purpose- In order to protect the place and reliability of the accounting profession in the society and the reputation of the profession, accountants should be knowledgeable about professional ethics in addition to their technical knowledge and skills, and they should comply with ethical rules and behave ethically. For this reason, it is important to determine the extent to which future accounting profession candidates include this issue in their postgraduate thesis studies in order to draw attention to the issue. The aim of this study is to examine the general situation of thesis studies written in the field of accounting ethics in Turkey in terms of different variables and to reveal their contribution to the literature. Methodology- Content analysis method, which is one of the qualitative analysis techniques, was used as a method in the study. The population of the study consists of master's and doctoral theses completed in the field of accounting ethics registered in the database of the Council of Higher Education Thesis Documentation Centre (YÖKTEZ). Seventeen theses written between 2006 and 2023 in the field of accounting ethics were analysed in terms of different variables. Findings- According to the findings obtained from the study, it was concluded that the first thesis in the field of accounting ethics was written in 2006, the majority of the theses written were at the master's level, and the most thesis on the subject was completed in 2021. It was observed that most theses on accounting ethics were completed at Muğla Sıtkı Koçman University and Sakarya University, and the majority of thesis advisors had the title of Dr. Faculty Member. It was observed that the survey method, one of the quantitative research methods, was mostly preferred as a method in the studies. In 15 different universities, it was seen that the subject of accounting ethics was included in postgraduate education. It is seen that the keywords preferred in the theses are concentrated on the concepts of ethics, accounting ethics, professional ethics, accounting, behavioural accounting and earnings management. Conclusion-The fact that the majority of the theses written are master's theses shows that more doctoral theses are needed to expand the field. In addition, considering the number of universities in Turkey and the number of universities providing postgraduate education in the field of accounting, it will be seen that the number of theses on this subject is quite limited
Keywords: Finance; Finans; Business Administration; İşletme